Efektivitas Pendidikan Kesehatan dengan Media Audio Visual Terhadap Tingkat Pengetahuan Cuci Tangan Pakai Sabun Sebagai Upaya Pencegahan Covid-19 Pada Anak Usia Dini di TK Amzar Molinow Kota Kotamobagu: The Effectiveness of Health Education with Audio Visual Media on Knowledge Levels of Hand Washing with Soap as an Effort to Prevent Covid-19 in Early Childhood in Amzar Molinow Kindergarten Kotamobagu City - Eys Novianti.s; Luvi Dian Afriyani (Journal of Holistics and Health Sciences (JHHS), 2022)
The impact of Covid-19 on children can affect physical health. Data for the Covid-19 cluster in Kotamobagu City Regency as of September 2021, 14 positive cases in the 1-6 year age group. Oral education is still a lack of action causing a lack of student knowledge. An alternative way to overcome this problem is to conduct health education using audio-visual media. The purpose of the study was to find out how the effectiveness of health education with audio-visual media on the level of knowledge of hand washing with soap. Types of Quasy Experimental Research, One Group Design Pretest-Posttest. Total Sampling 22 respondents. questionnaire sheet 7 steps to wash hands with soap. Univariate analysis of knowledge before health education was carried out with audio-visual media in the category of lack of knowledge, 11 respondents with good knowledge, 3 respondents, after increasing the category of good knowledge, 13 respondents with poor knowledge, 4 respondents. Bivariate analysis Wilcoxon t-Test P = 0.000 kurang dari α 0.05, there is a significant effect on the effectiveness of health education with audio-visual media on the level of knowledge, so H0 is rejected, because the average value of respondents' knowledge before health education is 7.50 to 0 after conducting health education with audio-visual media on the level of knowledge of hand washing with soap. It is hoped that the school will implement health education with audio-visual media in schools in increasing students' knowledge to actively wash their hands with soap to avoid various diseases during the COVID-19 pandemic ABSTRAK Dampak Covid-19 terhadap anak dapat mempengaruhi kesehatan fisik. Data gugus Covid-19 Kabupaten Kota Kotamobagu perSeptember 2021 14 kasus positif kelompok usia 1-6 tahun. Edukasi secara lisan masih kurangnya tindakan menyebabkan kurangnya pengetahuan siswa. Cara alternatif mengatasi permasalahan ini melakukan pendidikan kesehatan menggunakan media audio visual. Tujuan penelitian mengetahui bagaimana efektifitas pendidikan kesehatan dengan media audio visual terhadap tingkat pengetahuan cuci tangan pakai sabun. Jenis Penelitian Quasy Ekperimental , One Group Design Pretest-Posttest. Total Sampling 22 responden. lembar kuesioner 7 langkah cuci tangan pakai sabun. Analisa univariat pengetahuan sebelum dilakukan pendidikan kesehatan dengan media audio visual kategori pengetahuan kurang 11 responden pengetahuan baik 3 responden, setelah dilakukan meningkat kategori pengetahuan baik 13 responden pengetahuan kurang 4 responden. Analisa Bivariat uji Wilcoxon t-Test P=0,000 kurang dari α 0,05, terdapat pengaruh signifikan terhadap efektifitas pendidikan kesehatan dengan media audio visual terhadap tingkat pengetahuan, sehingga H0 ditolak, Karena nilai rata-rata pengetahuan responden sebelum dilakukan pendidikan kesehatan yaitu 7.50 menjadi 0 sesudah dilakukan pendidikan kesehatan dengan media audio visual terhadap tingkat pengetahuan cuci tangan pakai sabun. Diharapkan pihak sekolah menerapkan pendidikan kesehatan dengan media audio visual disekolah dalam meningkatkan pengetahuan siswa untuk aktif melakukan cuci tangan pakai sabun agar terhindar dari berbagai penyakit dimasa pandemi covid-19.